The Potential Therapeutic Application of Peptides and Peptidomimetics in Cardiovascular Disease - Recio, Carlota; Maione, Francesco; Iqbal, Asif J.; Mascolo, Nicola; De Feo, Vincenzo (Frontiers in Pharmacology, 2017)
Cardiovascular disease (CVD) remains a leading cause of mortality and morbidity worldwide. Numerous therapies are currently under investigation to improve pathological cardiovascular complications, but yet, there have been very few new medications approved for intervention/treatment. Therefore, new approaches to treat CVD are urgently required. Attempts to prevent vascular complications usually involve amelioration of contributing risk factors and underlying processes such as inflammation, obesity, hyperglycaemia, or hypercholesterolemia. Historically, the development of peptides as therapeutic agents has been avoided by the Pharmaceutical industry due to their low stability, size, rate of degradation, and poor delivery. However, more recently, resurgence has taken place in developing peptides and their mimetics for therapeutic intervention. As a result, increased attention has been placed upon using peptides that mimic the function of mediators involved in pathologic processes during vascular damage. This review will provide an overview on novel targets and experimental therapeutic approaches based on peptidomimetics for modulation in CVD. We aim to specifically examine apolipoprotein A-I (apoA-I) and apoE mimetic peptides and their role in cholesterol transport during atherosclerosis, suppressors of cytokine signaling (SOCS)1-derived peptides and annexin-A1 as potent inhibitors of inflammation, incretin mimetics and their function in glucose-insulin tolerance, among others. With improvements in technology and synthesis platforms the future looks promising for the development of novel peptides and mimetics for therapeutic use. However, within the area of CVD much more work is required to identify and improve our understanding of peptide structure, interaction, and function in order to select the best targets to take forward for treatment.